Virtual classrooms and real connections: nurturing social skills in the digital age - Mohd Shariff, Sazlin Suhalmie; Mohamad, Masilah; Ya'acob, Fatin Farazh (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The shift to virtual learning has transformed education, offering flexibility and access like never before. However, while these changes bring many benefits, they also present new challenges, particularly in developing children's social skills. In traditional classrooms, social interaction happens naturally through daily face-to-face engagement. In contrast, digital learning environments require deliberate effort to create those opportunities. As online learning becomes an integral part of modern education, we are exploring how to foster genuine connections and emotional growth for children in a virtual world.